2009
DOI: 10.1200/jco.2009.23.6075
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon Alfa-2a Yields High Rates of Hematologic and Molecular Response in Patients With Advanced Essential Thrombocythemia and Polycythemia Vera

Abstract: A B S T R A C T PurposeWe conducted a phase II study of pegylated interferon alfa-2a (PEG-IFN-␣-2a) in patients with essential thrombocythemia (ET) and polycythemia vera (PV). Patients and MethodsSeventy-nine patients (40 with PV and 39 with ET) have been treated. Median time from diagnosis to PEG-IFN-␣-2a was 54 months in patients with PV and 33 months in patients with ET. Eighty-one percent of patients had received prior therapy. The first three patients received PEG-IFN-␣-2a at 450 g weekly. As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
290
3
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(311 citation statements)
references
References 35 publications
8
290
3
10
Order By: Relevance
“…Two recent studies of pegylated INF-a ( 90 mg SC weekly) in PV and ET reported hematologic remissions of 80% accompanied by decreases in JAK2V617F allele burden (complete molecular remission rate of 5-10%) [119,120]. In one of the two studies [119], 77 cases were evaluable after a median follow up of 21 months and 76% and 70% of patients with ET or PV, respectively, achieved a complete hematologic remission, mostly in the first 3 months; side effects were recorded in 96% of the patients and 22% had discontinued treatment. Controlled studies are needed to clarify the advantage (or disadvantage) of IFN therapy in PV, compared to hydroxyurea therapy.…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 99%
“…Two recent studies of pegylated INF-a ( 90 mg SC weekly) in PV and ET reported hematologic remissions of 80% accompanied by decreases in JAK2V617F allele burden (complete molecular remission rate of 5-10%) [119,120]. In one of the two studies [119], 77 cases were evaluable after a median follow up of 21 months and 76% and 70% of patients with ET or PV, respectively, achieved a complete hematologic remission, mostly in the first 3 months; side effects were recorded in 96% of the patients and 22% had discontinued treatment. Controlled studies are needed to clarify the advantage (or disadvantage) of IFN therapy in PV, compared to hydroxyurea therapy.…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 99%
“…Interestingly, the malignant clone tested in PV, as quantitated by the percentage of the mutated JAK2V617F, was reduced. 53,54 However, whether this drug is more efficacious than HU in reducing the rate of thrombosis remains to be demonstrated. The evidence to indicate IFN-a as the drug of choice in any ET and PV patient younger than 60 years and in hypercellular/early PMF 55 is not yet supported by clinical trials.…”
Section: What To Do In Young Patients With Thrombosismentioning
confidence: 99%
“…Cell-based quantitative assays are also useful to monitor treatment response, including assessment of minimal residual disease after allogenic stem cell transplantation. [53][54][55][56] Recent studies in PV have suggested the association of higher mutant allele burden with a higher risk of fibrotic transformation 57 and in PMF a lower mutant allele burden with inferior survival. 58,59 However, the lack of assay standardization across different laboratories undermines the practical translation of such observations, at present.…”
Section: Jak2 and Mpl Mutation Screening In Routine Clinical Practicementioning
confidence: 99%